2017
DOI: 10.1177/2055217317700668
|View full text |Cite
|
Sign up to set email alerts
|

Access and barriers to MS care in Latin America

Abstract: Multiple sclerosis (MS), an epidemiologically emergent disorder in Latin America (LATAM), poses substantial socioeconomic challenges to a region where most countries remain as economies in development. MS is not health priority despite its economic and communitarian impact with a relatively low prevalence. MS treatments in LATAM have evolved from earlier long-term oral steroids and immunosuppression protocols, to platform disease modifying therapies (DMTs), to the current landscape with more advanced therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
0
18
0
2
Order By: Relevance
“…In Latin America, medical societies have expressed concern about pharmacy-level substitution of biosimilars, 145,146 given its potential implications for pharmacovigilance and safety. 144 The product provided to the patient may be unknown to the recipient and the prescriber in many cases, 154 and substitution is a particular concern in countries where intended copies are in use. 2,84 Information on pharmacy-mediated substitution of biosimilars was collected for 13 Latin American countries in a 2017 global survey; Peru was the only country in the region for which it was indicated that substitution could occur.…”
Section: Implications and Considerations For Clinicians In Latin Americamentioning
confidence: 99%
“…In Latin America, medical societies have expressed concern about pharmacy-level substitution of biosimilars, 145,146 given its potential implications for pharmacovigilance and safety. 144 The product provided to the patient may be unknown to the recipient and the prescriber in many cases, 154 and substitution is a particular concern in countries where intended copies are in use. 2,84 Information on pharmacy-mediated substitution of biosimilars was collected for 13 Latin American countries in a 2017 global survey; Peru was the only country in the region for which it was indicated that substitution could occur.…”
Section: Implications and Considerations For Clinicians In Latin Americamentioning
confidence: 99%
“…A likely explanation for this finding, beyond the inherent nature of injectable drugs, is the interchangeability that has been observed in LATAM with the use of biosimilars. 2 , 12 , 13 …”
Section: Availability Of Dmts In Latammentioning
confidence: 99%
“…Once these biosimilars are commercially available, rigorous pharmacovigilance programs will be necessary to ensure that safety and efficacy is maintained. 12 However, these programs are nonexistent for most of the drugs in the majority of LATAM countries.…”
Section: Availability Of Dmts In Latammentioning
confidence: 99%
“…La esclerosis múltiple (EM) en Centroamérica y el Caribe mantiene una baja prevalencia 1 , mientras que el impacto socioeconómico ejercido por esta enfermedad en los sistemas de salud de la región es severo considerando el nivel de crecimiento económico de estos países. A pesar de esta limitación, en años recientes la mayoría de los sistemas de seguridad social y algunos de atención pública en esta zona han dedicado una gran porción de sus presupuestos a la adquisición de las variadas y onerosas terapias aprobadas por agencias internacionales para el manejo de la EM 2 . Esta situación se ha desarrollado gradualmente en respuesta institucional al clamor público apoyado por la necesidad neurológica de una atención moderna y adecuada de los pacientes con EM.…”
unclassified